NIRS Database on fresh blended cassava for DM, Water absorption, texture parameters & cooking time (OCT) at CIAT, Colombia - Tran, Thierry; Belalcazar Martinez, John Eiver (2023)
This is a database of quality traits of boiled cassava landraces, harvested at CIAT (Colombia) from two field trials: "Parentales/progenitors (36 genotypes)" and "Sensorial (28 genotypes)" in November 2019-February 2020. Five harvests were conducted: 19-63, 19-64 & 20-02 are from the field parentales in November 2019, December 2019 and January 2020 (9, 10, 11 months after planting), respectively; and 20-03 & 20-11 from field sensorial in January 2020 and February 2020 (10 and 11 months after planting). The dataset contains biophysical data (dry matter, water absorption, texture parameters, cooking time) and NIRS data of 160 samples. NIRS data was recorded on fresh blended cassava roots, using a Foss DS2500 instrument. The objective of the study is (1) to build a database of biophysical quality traits (DM, Water absorption, texture parameters & cooking time) and NIRS data collected on the same fresh roots samples; (2) Investigate correlations between biophysical data and NIRS data and develop predictive equations, in order to replace biophysical analyses with faster NIRS analyses. (2021-12-20)